2006
DOI: 10.1007/s00792-006-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Psychrobacter cryohalolentis K5 during growth at subzero temperatures

Abstract: It is crucial to examine the physiological processes of psychrophiles at temperatures below 4 degrees C, particularly to facilitate extrapolation of laboratory results to in situ activity. Using two dimensional electrophoresis, we examined patterns of protein abundance during growth at 16, 4, and -4 degrees C of the eurypsychrophile Psychrobacter cryohalolentis K5 and report the first identification of cold inducible proteins (CIPs) present during growth at subzero temperatures. Growth temperature substantiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 67 publications
5
41
1
Order By: Relevance
“…The genome of P. haloplanktis also reveals several insights into ROS protection such as deletion of ROS producing pathways, several occurrences of dioxygenases and the repair mechanisms of oxidized compounds (Medigue et al, 2005). Similar observations have been made in the genome and proteome of other psychrophilic microorganisms (Rabus et al, 2004;Medigue et al, 2005;Methe et al, 2005;Duchaud et al, 2007;Bakermans et al, 2007;Ayub et al, 2009;Piette et al, 2010), revealing a general constraint on these bacteria. However, we found that at 18 °C, another type of oxidative stress is induced by stimulation of metabolic activity.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The genome of P. haloplanktis also reveals several insights into ROS protection such as deletion of ROS producing pathways, several occurrences of dioxygenases and the repair mechanisms of oxidized compounds (Medigue et al, 2005). Similar observations have been made in the genome and proteome of other psychrophilic microorganisms (Rabus et al, 2004;Medigue et al, 2005;Methe et al, 2005;Duchaud et al, 2007;Bakermans et al, 2007;Ayub et al, 2009;Piette et al, 2010), revealing a general constraint on these bacteria. However, we found that at 18 °C, another type of oxidative stress is induced by stimulation of metabolic activity.…”
Section: Discussionsupporting
confidence: 80%
“…Cold shock proteins that have been identified as CAPs in P. haloplanktis include Pnp (+4x), TypA (+5x) and the trigger factor TF (+38x) that are involved in distinct functions (degradosome, membrane integrity and protein folding, respectively). Sustained synthesis of various cold shock protein-homologues has been also reported in other cold-adapted bacteria (Bakermans et al, 2007;Kawamoto et al, 2007;Bergholz et al, 2009). There are therefore striking similarities between the cold shock response in mesophiles and cold adaptation in psychrophiles.…”
Section: Cold Shock and Heat Shock Proteinsmentioning
confidence: 62%
See 1 more Smart Citation
“…Gene expression studies of both psychrotolerant and strict mesophiles growing at suboptimal temperatures have detected increased expression of proteins for destabilization of nucleic acid secondary structures, maintenance of membrane fluidity, chaperones, uptake of compatible solutes, and energy metabolism (2,36,47). However, reports of the global modifications to metabolism necessary for growth of psychrophiles at temperatures below 0°C remain rare (4,5). Analysis of the amino acid sequences and structures of psychrophilic enzymes has given rise to the flexibility concept, i.e., that a psychrophilic enzyme can exhibit increased catalytic activity at low temperature with limited loss of thermostability by adaptation for reduced numbers of stabilizing interactions between key amino acid residues (20,40).…”
mentioning
confidence: 99%
“…For analysis of the proteome, cells were harvested from the remaining 475 ml of the transcriptome sample culture and analyzed as described by Bakermans et al (5). Briefly, samples were centrifuged at 10,000 ϫ g in a Sorvall RC-5B refrigerated centrifuge at the culture temperature for 10 min.…”
mentioning
confidence: 99%